Gambaran Terapi Obat Pulang Pasien Geriatri Setelah Menjalani Rawat Inap Di Bangsal Penyakit Dalam Di RS Panti Wilasa Dr. Cipto Semarang - Triananingsih, Novi; NSH, Maria Caecilia; Rahmawati, Fita (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Geriatric patients are elderly patients (>60 years) who have various chronic diseases with polypharmacy that varies by age group. This study aims to determine the differences in the age of elderly patients according to age group in the internal medicine ward of Panti Wilasa RSUD Dr. Cipto. This study is a descriptive study with retrospective data collection on discharge prescriptions of geriatric patients after undergoing inpatient care in the internal medicine ward obtained from medical record data. Sampling used a purposive sampling technique. In this study were classified into three groups: age 60 to 74 years; age 75 to 90 years; and age > 90 years. During the study period 86% were aged 60-74 years and 14% were aged 75-90 years, while in this study there were no ages over 90 years. In this study the most common gender was male, namely in the 60-74 age group 50.5% while in the 75-90 age group 73.3%. The length of hospitalization in the 60-75 age group was 49.5% and the 75-90 age group 60%, namely 4-5 days. And the top 5 types of drugs that are widely used in this age group are omeprazole, aspirin, metoclopramide, spironolactone and warfarin. The number of diagnoses received by the age group 60-74 years with 2 diagnoses 34.7%, with 3 diagnoses 31.6%. While the number of diagnoses received by the age group 75-90 years with 2 diagnoses 40%, with 3 diagnoses 33.3%. This shows that elderly patients have the same therapeutic picture in terms of age group. Keywords: Geriatric Patients, Internal Medicine Ward, Polypharmacy, Chronic Disease.